Kandungan Gizi Makro Kerupuk Daun Kelor (Moringa oleifera) Sebagai Inovasi Cemilan Bergizi - Monica, Sarah; Laenggeng, Abd Hakim; Buntu, Amalia; Masrianih, Masrianih; Febriani, Vita Indri; Lilies, Lilies (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the amount of macronutrient content contained in Moringa leaf crackers (Moringa oleifera). This study used a Complete Random Design (RAL) and was an experimental study using moringa leaf flour formulations, namely F0 (0%), F1 (10%), F2 (15%), and F (20%) each treatment was repeated 3 times. The analysis data with the Analysis Of Variance (ANOVA) statistical test showed the real difference between treatments. Determination of protein content using the Anthrone method, protein content using the Biuret method, and determination of fat content using Soxhlet. The results showed that the carbohydrate content in the formula of 10% moringa leaf flour was 0.47%, the formula of 15% moringa leaf flour was 0.41%, the formula of 20% moringa leaf flour was 0.34%, the protein content in the formula of 10% moringa leaf flour was 0.262%, the formula of 15% moringa leaf flour was 0.313%, and the formula of 20% moringa leaf flour was 0.322%. The fat content in the 10% moringa leaf flour formula is 10.28%, the 15% moringa leaf flour formula is 13.76% and the 20% moringa leaf flour formula is 28.26%.